2012
DOI: 10.5664/jcsm.1786
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of CBTI to the Non-Sleep Specialist: Protocol Development and Training Issues

Abstract: Strong evidence supports the effi cacy of cognitive behavioral therapy for insomnia (CBTI). A signifi cant barrier to wide dissemination of CBTI is the lack of qualifi ed practitioners. We describe challenges and decisions made when developing a CBTI dissemination program in the Veterans Health Administration (VHA). The program targets mental health clinicians from different disciplines (psychiatry, psychology, social work, and nursing) with varying familiarity and experience with general principles of cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 62 publications
3
124
0
Order By: Relevance
“…[25][26][27] However, Manber and colleagues have described the successful training of mental health clinicians without sleep specialization to deliver CBTi in the VA healthcare system. 28 In response to this, shortened protocols (i.e., ≤ 4 sessions) have been developed, and research has shown them to be efficacious and effective in treating insomnia in adults of all ages (see McCrae, 29 Buysse,30 or Edinger and Sampson, 31 for review). For example, Edinger and Sampson demonstrated that four sessions of CBTi resulted in clinically significant improvements in wake after sleep onset, total wake time, and sleep efficiency compared to sleep hygiene recommendations alone.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…[25][26][27] However, Manber and colleagues have described the successful training of mental health clinicians without sleep specialization to deliver CBTi in the VA healthcare system. 28 In response to this, shortened protocols (i.e., ≤ 4 sessions) have been developed, and research has shown them to be efficacious and effective in treating insomnia in adults of all ages (see McCrae, 29 Buysse,30 or Edinger and Sampson, 31 for review). For example, Edinger and Sampson demonstrated that four sessions of CBTi resulted in clinically significant improvements in wake after sleep onset, total wake time, and sleep efficiency compared to sleep hygiene recommendations alone.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…The first is with patients who are undergoing or ready to engage in trauma-focused CBT for PTSD (either PE or CPT). This is because traumafocused CBT is demanding and intensive and adding another therapy that requires behavioral changes may hinder adherence (Manber et al [75]). Also, research reviewed here indicates that there is a reasonable chance that trauma-focused CBT will improve sleep.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…The CBTI protocol being disseminated takes into account the possibility that PTSD symptoms such as nocturnal hyperarousal and perceived need for vigilance may complicate standard application of CBTI (DeViva et al [44]) and necessitate special adaptation of the standard CBTI protocol. The protocol is anchored in case conceptualization (e.g., Persons [76]), taking into account factors that contribute to each patient's unique presentation (Manber et al [75]). Special considerations for the application of CBTI for patients with PTSD-related sleep problems include, among other things, cognitive therapy techniques such as cost-benefit analysis for addressing fear of going to sleep and presleep perimeter checks, methods for addressing hyperarousal, and interventions to decrease such maladaptive behavior following nightmare arousals as staying awake trying to figure out the meaning of a nightmare (Manber et al [75]).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the success of the Veterans Administration (VA) CBT-I training program has much to teach us. The question moving forward is how to export this level of dissemination from a self contained system like the VA to the open access Health care system that exists throughout the U.S [17].…”
Section: Moving Forwardmentioning
confidence: 99%